Amylase loading on a commercial nylon bandage intended for the control delivery of drug in treating localized wounds. (2021) - Olaniran, O.; Garcia, C.; Li, W.; Rumbaugh, Kendra
Abstract: Layer-by-Layer assembly process has been reported of the ability to construct a hydrolytically degradable drugs depot on a commercially available bandage, which can release the drug directly into a wound bed and dramatically change the gene exposure. In this work, a commercial bandage was coated with amylase via layer-by-layer (LbL) in order to obtain nanoscale layers of amylase for intended control drug delivery in treating localized wounds. Meanwhile, the commercial bandage was initially plasma-cleansed for five (5) minutes before it was mounted on to a dipping machine. LbL assembly using chitosan/carboxymethyl cellulose (CMC) was designed by alternate adsorption unto the commercial bandage. Furthermore, amylase was incorporated into the polymeric network of the film by using electrostatic interactions, hydrogen bonds and hydrophobic interactions. A carpet layer of 10 repeats of LbL was formed on the bandage by alternate coating of chitosan and carboxymethyl cellulose (CMC). On to this base layer, another 20 repeats was performed for loading of the amylase on to the base layer. Two solutions of amylase were used with the same concentration of 2 mg/ml, but different pHs of 4.5 and 5.8 in order to study the effect of pH on the nano-coating. Another 5 LbL repeats of chitosan/CMC was conducted in order to form the network of the self-assembled nano-coating LbL. The nano-coating was characterized by morphological and physico-chemical analyses in order to evaluate the multilayered structure. All the experiments were conducted at room temperature.